PENGARUH MOTIVASI TERHADAP KINERJA - Rus Sulistiawan (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2018)
Motivation is the process of determining the intensity, direction and perseverance of the individual to achieve the goal. Motivation can be sourced from within the employee in the form of awareness about the importance of the benefits of the work it does. And so does the motivation that comes from outside the employee concerned in the form of a condition that requires himto perform a job optimally. Human resource development is a process of improving the quality or ability in order to achieve the goal rate or level of development of the company must always be considered, therefore the company requires employees who have high discipline and have the motivation to further develop again. Motivation is very influential in the performance of employees who are the main motivation to motivate himself so that his performance will be better than ever and can carry out their duties properly, a motivation can be arousing and directing towards his behavior to achieve the expected goal of a company. This study aims to provide an overview of how the influence of motivation on employee performance.